2015
DOI: 10.1123/ijsnem.2015-0180
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation and Physical Performance in Adolescent Swimmers

Abstract: It is hypothesized that vitamin D insufficiency in athletes might negatively affect sport performance. The objective of this study was to examine the effect of vitamin D3 supplementation on physical performance of adolescent swimmers with vitamin D insufficiency. Fifty-three adolescent competitive swimmers with vitamin D insufficiency (serum 25-hydroxyvitamin-D concentrations (25(OH)D) < 30 ng/ml, mean 24.2 ± 4.8 ng/ml) were randomized to receive 2,000 IU/day of vitamin D3 or placebo for 12 weeks. Swimming per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…In our study, participants with 25(OH)D of 30 ng/mL or higher did not show better maintenance of normalized peak torque or RTD 20%–80% after ACLR when compared to those with concentrations of less than 30 ng/mL. Some studies supplementing athletes with vitamin D have not demonstrated efficacy in improving strength or functional outcomes ( 49 ). For instance, in one trial, adolescent swimmers with 25(OH)D of less than 30 ng/mL took vitamin D drops providing 2000 IU/day for 12 weeks with the goal of reaching 30 ng/mL.…”
Section: Discussioncontrasting
confidence: 54%
“…In our study, participants with 25(OH)D of 30 ng/mL or higher did not show better maintenance of normalized peak torque or RTD 20%–80% after ACLR when compared to those with concentrations of less than 30 ng/mL. Some studies supplementing athletes with vitamin D have not demonstrated efficacy in improving strength or functional outcomes ( 49 ). For instance, in one trial, adolescent swimmers with 25(OH)D of less than 30 ng/mL took vitamin D drops providing 2000 IU/day for 12 weeks with the goal of reaching 30 ng/mL.…”
Section: Discussioncontrasting
confidence: 54%
“…Additionally, Backx et al in their study reported similar results within three-month supplementation of 2200 IU VD3; however, higher concentration of 25(OH) VD3 was observed after 12 months of intervention [ 66 ]. In contrast, there are studies reporting the increased serum 25(OH)VD3 concentration compared to the baseline after 12 weeks of the supplementation with 2000 IU/day of VD3 [ 67 , 68 ]. It has been shown that inter-individual differences and genetic variation in VD3 binding protein affect the response to this supplementation [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of supplementation of vitamin D on exercise and muscle health have recently been reported in soccer and rugby players, elite ballet dancers, and in active adult males that were vitamin D insufficient at the baseline (113,(130)(131)(132)(133)(134)(135)(136) . Four studies (113,130,131,136) have found that supplementation of vitamin D significantly increased strength, power and exercise performance even with a small sample size, while three studies reported no significant effect of vitamin D on any physical parameter (132)(133)(134) . Further, a reduced injury incidence was reported in a group of elite ballet dancers following 4 months of 2000 IU/d of vitamin D supplementation (113) .…”
Section: Clinical Studies and Perspectivesmentioning
confidence: 99%
“…In contrast, recent metaanalyses have not been consistent with these outcomes, though many variables need to be considered when comparing studies, for example, the parameters analysed, age of the population, if participants live in residential institutions, dose and cut points of vitamin D, ethnicity, period of the intervention, instruments to assess Ca and vitamin D intake and sunlight exposure, and many others (129) . Another important variable to consider in supplementation studies is if the participant is classified as sufficient or deficient in vitamin D since the baseline period, as many of the biological effects of vitamin D are evident when status of vitamin D is corrected from deficient to normal levels (113,122,(130)(131)(132)(133)(134)(135)(136)(137) .…”
Section: Clinical Studies and Perspectivesmentioning
confidence: 99%